The Statutes at Large of South Carolina: Edited Under Authority of the Legislature 417 (1840) - (:unkn) unknown (My University, 1743)
"every white male inhabitant of this Province... who shall, on any Sunday or Christmas day in the year, go and resort to any church or any other public place of divine worship within this Province, and shall not carry with him a gun or a pair of horse pistols, in good order and fit for service, with at least six charges of gun-powder and ball, and shall not carry the same into the church or other place of divine worship as aforesaid, every such person shall forfeit and pay the sum of twenty shillings, current money, for every neglect of the same."
Keywords: REQUIRED POSSESSION